Validity of the Community Periodontal Index of Treatment Needs' (CPITN) for population periodontitis screening Validação do Community Periodontal Index of Treatment Needs' (CPITN) para identificação de periodontite em populações - Diego Garcia Bassani; Carina Maciel da Silva; Rui Vicente Oppermann (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2006)
The aim of the present study was to validate two versions of CPITN for periodontitis diagnosis. A sample of 400 individuals underwent full mouth periodontal examination including Clinical Attachment Loss, Periodontal Pocket Depth, and Sub-gingival Calculus. Full and partial CPITN versions were derived from this exam (gold standard). Contingency tables were constructed and operational characteristics obtained, as well as ROC curves. The results show 58% sensitivity for full CPITN and 80.6% specificity. Positive and negative predictive values were 87% and 46.3%, respectively. According to the test, estimated periodontitis prevalence was 46%, while the figure obtained with the gold standard was 69%. The partial version of the CPITN showed 50% sensitivity and 87.1% specificity. Positive and negative predictive values were 89.6% and 43.9%, respectively. Estimated periodontitis prevalence, through partial CPITN, was 30.5%. Adjusted global agreement (kappa) for partial and full CPITN was 0.32 and 0.29, respectively. Both CPITN versions disagreed significantly with gold standard results (chi-square p < 0.001). As a conclusion, both total and partial CPITN failed to reflect the real periodontal status of the sample. Visando validar duas versões do CPITN para o diagnóstico de periodontite em estudos populacionais, 400 indivíduos foram submetidos a exames de perda de inserção clínica, profundidade de sondagem e presença de cálculo subgengival. A versão parcial e completa do CPITN foi derivada deste exame e comparada com o mesmo (padrão-ouro). Tabelas de contingência foram elaboradas e obtiveram-se as características operacionais do CPITN. Os resultados mostram sensibilidade de 58% e especificidade de 80,6% para a versão completa. Os valores preditivos positivo e negativo foram 87% e 46,3% respectivamente. A prevalência de periodontite estimada por esta versão foi 46% enquanto que o valor de referência segundo o padrão-ouro foi 69%. A versão parcial demonstrou uma sensibilidade de 50% e uma especificidade de 87,1%. Os valores preditivos positivo e negativo foram, respectivamente, 89,6% e 43,9%. A prevalência estimada de periodontite foi 30,5%. A taxa global ajustada de concordância (kappa) para a versão parcial e completa foi, respectivamente, 0,32 e 0,29. Ambas as versões discordaram dos resultados do padrão-ouro (qui-quadrado p < 0,001). Ambas as versões do CPITN falharam em representar o status periodontal da amostra.